Maritime English: Teaching English for Maritime Sciences or Teaching Maritime Sciences in English? - Dhion Meitreya Vidhiasi; Syihabuddin Syihabuddin (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
Maritime English is a “scourge” for maritime science students at universities engaged in maritime science. English is a foreign language in Indonesia may cause the students cannot understand Maritime English well. A phenomenon occurs that Maritime English teachers do not have basic knowledge about the maritime sciences. This has an impact on the teaching and learning process of Maritime English. This study seeks to reveal whether Maritime English is English teaching intended for maritime science or Maritime English is actually maritime science materials taught using English. The researcher uses a qualitative descriptive method by using a learning module adopted from the IMO Model Course 3.17 to conduct research. The results of the study found that the teachers never obtained many materials related to the maritime world. However, there are also materials that these teachers obtained during their undergraduate and master’s degree courses, such as grammar, reading comprehension, and listening comprehension. This means that Maritime English is indeed English intended for maritime science students (English for Special Purposes) and maritime sciences delivered using English.